2012
DOI: 10.1371/journal.pone.0050336
|View full text |Cite
|
Sign up to set email alerts
|

The Eye in the Sky: Combined Use of Unmanned Aerial Systems and GPS Data Loggers for Ecological Research and Conservation of Small Birds

Abstract: Technological advances for wildlife monitoring have expanded our ability to study behavior and space use of many species. But biotelemetry is limited by size, weight, data memory and battery power of the attached devices, especially in animals with light body masses, such as the majority of bird species. In this study, we describe the combined use of GPS data logger information obtained from free-ranging birds, and environmental information recorded by unmanned aerial systems (UASs). As a case study, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 33 publications
(42 reference statements)
1
63
0
2
Order By: Relevance
“…As the technology has progressed, so has the sophistication of its applications to habitat research and monitoring, such as expeditious imaging of agricultural habitats overflown by foraging lesser kestrels (Falco naumanni) equipped with GPS data loggers (Rodriguez et al 2012), and modelling fine-scale distribution of tuberculosis-carrying ungulates based on UAS surveys of a variety of habitats in Donana National Park, Spain (Barasona et al 2014). Because of the unparalleled spatial resolution achievable in UAS imagery, it may also be used to "ground-truth" coarser-resolution satellite imagery (Watts et al 2010).…”
Section: Uas For Wildlife Habitat Research and Monitoringmentioning
confidence: 99%
“…As the technology has progressed, so has the sophistication of its applications to habitat research and monitoring, such as expeditious imaging of agricultural habitats overflown by foraging lesser kestrels (Falco naumanni) equipped with GPS data loggers (Rodriguez et al 2012), and modelling fine-scale distribution of tuberculosis-carrying ungulates based on UAS surveys of a variety of habitats in Donana National Park, Spain (Barasona et al 2014). Because of the unparalleled spatial resolution achievable in UAS imagery, it may also be used to "ground-truth" coarser-resolution satellite imagery (Watts et al 2010).…”
Section: Uas For Wildlife Habitat Research and Monitoringmentioning
confidence: 99%
“…Instead, the focus is on the use of small drones in precision agriculture (e.g., [46,53,54]) and vegetation monitoring in rangelands (e.g., [44,[55][56][57][58][59]). Other environmental research applications found in the literature include biodiversity monitoring [60][61][62][63][64], habitat monitoring [65][66][67], and soil properties [68,69]. Another application that can assist in environmental monitoring is the generation of high spatial resolution digital surface/elevation models from drone imagery [70,71].…”
Section: The Use Of Small Drones For Environmental Mapping and Monitomentioning
confidence: 99%
“…a few hundred to a few thousand US$), and this is currently leading to their widespread use for wildlife observations [2,3]. In ornithology, fixed-wing drones are already being widely used for census work and observations [4,5], and dozens of videos available on the Internet testify that researchers, and the general public, are keen to use drones to approach birds. In a number of countries, air traffic regulations strictly control the civil use of drones, yet no ethical guidelines exist with respect to their potential impacts on animal welfare.…”
Section: Introductionmentioning
confidence: 99%